Difference between revisions of "009B Sample Final 1, Problem 7"
Jump to navigation
Jump to search
Line 1: | Line 1: | ||
− | + | <span class="exam">(a) Find the length of the curve | |
− | + | ::<math>y=\ln (\cos x),~~~0\leq x \leq \frac{\pi}{3}</math>. | |
− | + | <span class="exam">(b) The curve | |
− | + | ::<math>y=1-x^2,~~~0\leq x \leq 1</math> | |
− | + | <span class="exam">is rotated about the <math style="vertical-align: -3px">y</math>-axis. Find the area of the resulting surface. | |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |'''1.''' The formula for the length <math style="vertical-align: 0px">L</math> of a curve <math style="vertical-align: -5px">y=f(x)</math> where <math style="vertical-align: -3px">a\leq x \leq b</math> is |
|- | |- | ||
| | | | ||
− | + | <math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math> | |
|- | |- | ||
− | | | + | |'''2.''' Recall |
− | |||
|- | |- | ||
− | | | + | | <math style="vertical-align: -14px">\int \sec x~dx=\ln|\sec(x)+\tan(x)|+C.</math> |
− | |||
|- | |- | ||
− | | | + | |'''3.''' The surface area <math style="vertical-align: 0px">S</math> of a function <math style="vertical-align: -5px">y=f(x)</math> rotated about the <math style="vertical-align: -4px">y</math>-axis is given by |
− | |||
|- | |- | ||
| | | | ||
− | + | <math style="vertical-align: -13px">S=\int 2\pi x\,ds,</math> where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}.</math> | |
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 37: | Line 35: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we calculate& | + | |First, we calculate <math>\frac{dy}{dx}.</math> |
|- | |- | ||
− | |Since <math style="vertical-align: -5px">y=\ln (\cos x),</math> | + | |Since <math style="vertical-align: -5px">y=\ln (\cos x),</math> |
|- | |- | ||
− | | | + | | <math>\frac{dy}{dx}=\frac{1}{\cos x}(-\sin x)=-\tan x.</math> |
− | |||
|- | |- | ||
|Using the formula given in the Foundations section, we have | |Using the formula given in the Foundations section, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>L=\int_0^{\pi/3} \sqrt{1+(-\tan x)^2}~dx.</math> | |
|} | |} | ||
Line 53: | Line 50: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we have | + | |Now, we have |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
L & = & \displaystyle{\int_0^{\pi/3} \sqrt{1+\tan^2 x}~dx}\\ | L & = & \displaystyle{\int_0^{\pi/3} \sqrt{1+\tan^2 x}~dx}\\ | ||
&&\\ | &&\\ | ||
Line 73: | Line 70: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
L& = & \ln |\sec x+\tan x|\bigg|_0^{\frac{\pi}{3}}\\ | L& = & \ln |\sec x+\tan x|\bigg|_0^{\frac{\pi}{3}}\\ | ||
&&\\ | &&\\ | ||
Line 82: | Line 79: | ||
& = & \displaystyle{\ln (2+\sqrt{3})}. | & = & \displaystyle{\ln (2+\sqrt{3})}. | ||
\end{array}</math> | \end{array}</math> | ||
+ | |- | ||
+ | | | ||
|} | |} | ||
Line 89: | Line 88: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We start by calculating& | + | |We start by calculating <math>\frac{dy}{dx}.</math> |
|- | |- | ||
− | |Since <math style="vertical-align: - | + | |Since <math style="vertical-align: -5px">y=1-x^2,</math> |
+ | |- | ||
+ | | <math>\frac{dy}{dx}=-2x.</math> | ||
|- | |- | ||
|Using the formula given in the Foundations section, we have | |Using the formula given in the Foundations section, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>S\,=\,\int_0^{1}2\pi x \sqrt{1+(-2x)^2}~dx.</math> | |
|} | |} | ||
Line 102: | Line 103: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math> | + | |Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math> |
|- | |- | ||
− | |We proceed by using trig substitution. Let <math style="vertical-align: -13px">x=\frac{1}{2}\tan \theta.</math> Then, <math style="vertical-align: -12px">dx=\frac{1}{2}\sec^2\theta \,d\theta.</math> | + | |We proceed by using trig substitution. |
+ | |- | ||
+ | |Let <math style="vertical-align: -13px">x=\frac{1}{2}\tan \theta.</math> Then, <math style="vertical-align: -12px">dx=\frac{1}{2}\sec^2\theta \,d\theta.</math> | ||
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int 2\pi \bigg(\frac{1}{2}\tan \theta\bigg)\sqrt{1+\tan^2\theta}\bigg(\frac{1}{2}\sec^2\theta\bigg) d\theta}\\ | \displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int 2\pi \bigg(\frac{1}{2}\tan \theta\bigg)\sqrt{1+\tan^2\theta}\bigg(\frac{1}{2}\sec^2\theta\bigg) d\theta}\\ | ||
&&\\ | &&\\ | ||
Line 119: | Line 122: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | |Now, we use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=\sec \theta.</math> Then, <math style="vertical-align: -1px">du=\sec \theta \tan \theta \,d\theta.</math> | + | |Now, we use <math style="vertical-align: 0px">u</math>-substitution. |
+ | |- | ||
+ | |Let <math style="vertical-align: 0px">u=\sec \theta.</math> Then, <math style="vertical-align: -1px">du=\sec \theta \tan \theta \,d\theta.</math> | ||
|- | |- | ||
|So, the integral becomes | |So, the integral becomes | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int \frac{\pi}{2}u^2du}\\ | \displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int \frac{\pi}{2}u^2du}\\ | ||
&&\\ | &&\\ | ||
Line 141: | Line 146: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
S & = & \displaystyle{\int_0^1 2\pi x \sqrt{1+4x^2}~dx}\\ | S & = & \displaystyle{\int_0^1 2\pi x \sqrt{1+4x^2}~dx}\\ | ||
&&\\ | &&\\ | ||
Line 151: | Line 156: | ||
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | '''(a)''' <math>\ln (2+\sqrt{3})</math> | + | | '''(a)''' <math>\ln (2+\sqrt{3})</math> |
|- | |- | ||
− | | '''(b)''' <math>\frac{\pi}{6}(5\sqrt{5}-1)</math> | + | | '''(b)''' <math>\frac{\pi}{6}(5\sqrt{5}-1)</math> |
|} | |} | ||
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Revision as of 08:46, 10 April 2017
(a) Find the length of the curve
- .
(b) The curve
is rotated about the -axis. Find the area of the resulting surface.
Foundations: |
---|
1. The formula for the length of a curve where is |
|
2. Recall |
3. The surface area of a function rotated about the -axis is given by |
where |
Solution:
(a)
Step 1: |
---|
First, we calculate |
Since |
Using the formula given in the Foundations section, we have |
|
Step 2: |
---|
Now, we have |
|
Step 3: |
---|
Finally, |
|
(b)
Step 1: |
---|
We start by calculating |
Since |
Using the formula given in the Foundations section, we have |
|
Step 2: |
---|
Now, we have |
We proceed by using trig substitution. |
Let Then, |
So, we have |
|
Step 3: |
---|
Now, we use -substitution. |
Let Then, |
So, the integral becomes |
|
Step 4: |
---|
We started with a definite integral. So, using Step 2 and 3, we have |
|
Final Answer: |
---|
(a) |
(b) |